Study Antiulcer And Possible Gastroprotective Mechanisms Of Musa Pulp ABB SPP - Boffill Cárdenas, María de los Angeles; Martín Calero, María José; Valido Díaz, Arianna; Garrido Arce, Carmen (Revista Cubana de Investigaciones Biomédicas, 2019)
The objective of this work was to evaluate in a model of chronic ulcer the antiulcer effect and the possible mechanisms by which this fruit produces gastroprotection. The pulp of the green fruit was sliced, dried at 50 oC, ground and sieved. Ninety Male Wistar rats of 190 ± 10 g were used. The antiulcer effect of pulp was performed with the chronic model of ulcer by acetic acid, used 5 groups of 8 animal, the suspension of the pulp at 125; 250; 500 mg / kg BW were applied 72 hours after inducing the ulcer for 7 days. For the determination of the mechanisms, also 5 groups of 10 animal were used, the banana pulp was supplied in a dose of 125, 250 and 500 mg / kg of BW, for three days, before inducing the ulcers with indomethacin, the activity of the myeloperoxidase, the superoxide dismutase and the levels of prostaglandins in the gastric mucosa were determined. Treatment with the suspensions of the pulp in the chronic ulcer model reduced in a very highly significant way the damaged area in all the treated groups and this reduction was greater than that produced by ranitidine; there was a significant decrease in myeloperoxidase only with the highest dose tested and a significant increase of superoxide dismutase and prostaglandins level with all the doses used. We conclude that the pulp preparations provoked an intense anti-ulcer. The mechanism of gastroprotective action was mediated by an antioxidant effect and mucosal protection.